Efectos de los niveles de fertilización orgánica y química en el desarrollo de plántulas de teca (tectona grandis l.f.), en el Cantón Mocache, año 2016 - López Bustamante, Jairo Rolando (2016)
The quality of the seedlings directly influences the initial growth and yield of any forest plantation. An established plantation with low quality seedlings and without vigor will end up being a failure. Therefore, it is important that the seedlings receive all the necessary care, so that a good start and initial development can be guaranteed, once established in the planting site. The objective of this project was to evaluate the effect of organic and chemical fertilization on the development of Tectona grandis (teak) seedlings. The variables of growth in diameter and height, number of leaves, leaf length, root length and survival of teak seedlings, with chemical and organic foliar fertilization were measured. Once the field data were recorded they were analyzed using the Excel spreadsheet and SAS software, 2004. The results show that the chemical fertilizer let obtain major means of the growth than the organic fertilizer and witness.